The effect of growth in murabahah finance on profitability (Study on Bank Pembiayaan Rakyat Syari’ah (BPRS) Bhakti Sumekar Sumenep) - Hertin Khalifatun Nisa Arifah,; Rachmad Hidayat, (Technium Social Sciences Journal, 2023)
This study aims to empirically prove the growth of musyarakah financing on the profitability of the Syari'ah Bhakti Sumekar Sumenep People's Financing Bank. Determination of the sample using purposive sampling method. The data used are 40 quarterly financial reports with data analysis methods using simple linear regression. The results showed that the growth of murabahah financing had an effect on the profitability of the Syari'ah Bhakti Sumekar Sumenep People's Financing Bank which was proxied by ROA.